Современный ремонт квартиры и дома своими руками: [справочник] / В.Л. Мигин ; [ ; ред. О. В. Марчукова; худож. Л.Е. Колесниченко] - Мигин Василий Леонидович ([БАО], 2007)
Экземпляры: аб. (2008) / Инвентарный номер: 52152 / Цена: / Сис.шифр: 38.683 / Авт.знак: М 57 / ГРНТИ: 67.29.29 / ББК: 38.683